Pengaruh Job Stress terhadap Job Satisfaction dan Organizational Commitment di Mediasi oleh Psychological Wellbeing Karyawan Perusahaan Facility Services di Tangerang Selatan - Ziliwu, Hendik Arianto; Tanuwijaya, Justine; Gunawan, Andreas Wahyu (J-MAS (Jurnal Manajemen dan Sains), 2024)
This research aims to investigate the influence of job stress on job satisfaction and organizational commitment, mediated by employees' psychological well-being. The study employs a quantitative method with a sample of 150 respondents from a Facility Services company. Data analysis is conducted using SPSS 25 for Windows. The findings reveal a significant negative influence of job stress on job satisfaction, a significant negative influence of job stress on psychological well-being, a significant negative influence of job stress on organizational commitment. There is a significant positive influence of psychological well-being on job satisfaction, a significant positive influence of psychological well-being on organizational commitment, and a significant positive influence of job satisfaction on organizational commitment. Psychological well-being fully and significantly mediates the relationship between job stress and both job satisfaction and organizational commitment.